Biochemistry - Champe, Pamela C.; Harvey, Richard A., Ph. D.; Ferrier, Denise R. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2008)
Biochemistry has been the best-selling medical-level biochemistry review book on the market for the past ten years. The book is beautifully designed and executed, and renders the study of biochemistry enormously appealing to medical students and various allied health students. It has over 125 USMLE-style questions with answers and explanations, as well as over 500 carefully-crafted illustrations. The Third Edition includes end-of-chapter summaries, illustrated case studies, and summaries of key diseases.
Unit IV: Nitrogen metabolism. Amino acids: disposal of nitrogen ; Amino acid degradation and synthesis ; Conversion of amino acids to specialized products ; Nucleotide metabolism -- Unit V: Integration of metabolism. Metabolic effects of insulin and glucagon ; The feed/fast cycle ; Diabetes mellitus ; Obesity ; Nutrition ; Vitamins -- Unit VI: Storage and expression of genetic information. DNA structure, replication and repair ; RNA structure, synthesis and processing ; Protein synthesis ; Regulation of gene expression ; Biotechnology and human disease.
Includes index.
Keywords: Biochemistry -- Outlines, syllabi, etc; Biochemistry -- Examinations, questions, etc; Clinical biochemistry -- Outlines, syllabi, etc; Clinical biochemistry -- Examinations, questions, etc; Biochemistry -- Examination Questions; Biochemistry -- Outlines